2012
DOI: 10.1128/jb.06817-11
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic p -Coumarate Degradation by Rhodopseudomonas palustris and Identification of CouR, a MarR Repressor Protein That Binds p -Coumaroyl Coenzyme A

Abstract: The phenylpropanoid p-coumarate and structurally related aromatic compounds are produced in large amounts by green plants and are excellent carbon sources for many soil bacteria. Aerobic bacteria remove the acyl side chain from phenylpropanoids to leave an aromatic aldehyde, which then enters one of several possible central pathways of benzene ring degradation. We investigated the pathway for the anaerobic degradation of p-coumarate by the phototrophic bacterium Rhodopseudomonas palustris and found that it als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 47 publications
2
78
0
Order By: Relevance
“…Although MarR proteins were originally described as regu- lators for multidrug and stress resistance genes, e.g., MarR for marAB in E. coli (31) and MexR for mexAB in P. aeruginosa (32), there are also MarR regulators that control aromatic compound metabolism (33)(34)(35)(36)(37). In general, the ligands for these proteins are ϳ100-Da-sized small molecules like protocatechuate and 4-hydroxybenzoic acid, but recently a number of studies showed that there are MarR members which bind CoA-thioesterified phenyl propanoids, including p-coumaroyl-CoA for CouR from R. palustris (20,38,39). We show that BadR binds a nonphenolic CoA-thioesterified compound.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although MarR proteins were originally described as regu- lators for multidrug and stress resistance genes, e.g., MarR for marAB in E. coli (31) and MexR for mexAB in P. aeruginosa (32), there are also MarR regulators that control aromatic compound metabolism (33)(34)(35)(36)(37). In general, the ligands for these proteins are ϳ100-Da-sized small molecules like protocatechuate and 4-hydroxybenzoic acid, but recently a number of studies showed that there are MarR members which bind CoA-thioesterified phenyl propanoids, including p-coumaroyl-CoA for CouR from R. palustris (20,38,39). We show that BadR binds a nonphenolic CoA-thioesterified compound.…”
Section: Discussionmentioning
confidence: 99%
“…Next, badR together with the gdh (glyceraldehyde-3-phosphase dehydrogenase) promoter was cut out by KpnI-XbaI digestion and ligated into pBBR1MCS-2 (22). The C-terminal His 6 -tagged BadM expression plasmid pQF5016b.badM was constructed by PCR amplification of badM from genomic DNA using primers badM-F and badM-R, followed by ligation into NcoI-BamHI-digested pQF5016b.rpa1794 plasmid (20). The plasmid constructions were confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, CouR is similar to CouR of Rhodopseudomonas palustris and FerC of Sphingobium sp. strain SYK-6, two MarR family transcriptional regulators whose ligands are p-hydroxycinnamoyl-CoAs (33,34). Therefore, it is likely that CouR represses the transcription of the cou genes and that p-hydroxycinnamoyl-CoA acts as its effector.…”
Section: Growth Of Rha1 On P-hydroxycinnamatesmentioning
confidence: 99%